Psychiatry Reform and the Espírito Santo Custodial Psychiatric Treatment Unitto - Gomes, Guilherme Ramos Hamer; Moura, Renata Theophilo da Costa; Herkenhoff , Henrique Geaquinto; Luciana Souza Borges Herkenhoff, Luciana Souza Borges Herkenhoff (Argumentum, 2021)
The article analyzes the connection between Law 10,216/2001 and security measures in the Espírito Santo Custodial Psychiatric Treatment Unit, aiming to question the application of the law in this context. The theoretical framework is composed of critical criminology and is based on an anti-asylum public health perspective. A deductive methodology, bibliographic and documentary analysis, and open questionnaires were utilized. Although there have been efforts towards humanization and training since 2017, severe deficiencies in the state’s Psychosocial Care Network were reported as obstacles to justifying the existence of the custodial unit, and as a disrupting factor countering the actions required to release patients from this mode of treatment. The expansion of ambulatory treatment in the state is, therefore, required and the full implementation of the Ordinance nº 94 MS 01/2014.